2007
DOI: 10.4049/jimmunol.179.3.1901
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chemokine Receptors, Including CCR6 and CXCR3, Regulate Antigen-Induced T Cell Homing to the Human Asthmatic Airway

Abstract: Human allergic asthma is a chronic inflammatory disease of the airways thought to be driven by allergen-specific Th2 cells, which are recruited into the lung in response to inhaled allergen. To identify chemoattractant receptors that control this homing pattern, we used endobronchial segmental allergen challenge in human atopic asthmatics to define the pattern of chemoattractant receptor expression on recruited T cells as well as the numbers of recruited CD1d-restricted NKT cells and levels of chemokines in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
74
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 54 publications
11
74
1
Order By: Relevance
“…The data described in this study confirm previously reported results that showed a decrease in CCR6 and CXCR3 expression on CD4 + bronchial T cells following segmental allergen challenge of human atopic asthmatic patients (56). However, it was hypothesized from the latter results that these receptors were internalized due to their encounter with their respective ligands in the airways, not taking into account the direct effect of T cell activation on CCR6 expression, as underscored in the current study.…”
Section: Discussionsupporting
confidence: 80%
“…The data described in this study confirm previously reported results that showed a decrease in CCR6 and CXCR3 expression on CD4 + bronchial T cells following segmental allergen challenge of human atopic asthmatic patients (56). However, it was hypothesized from the latter results that these receptors were internalized due to their encounter with their respective ligands in the airways, not taking into account the direct effect of T cell activation on CCR6 expression, as underscored in the current study.…”
Section: Discussionsupporting
confidence: 80%
“…The availability of multiple reagents active in various assays to identify and for manipulating iNKT cells will enable understanding their role in different patient population subsets (e.g. patients with various cancers [39], adult and pediatric acute versus chronic asthmatics, untreated or on various treatments [40][41][42][43][44][45]) and their various tissues, as well as intervening therapeutically. Given that several approaches to exploit iNKT cells have entered clinical trials [46,47], development of such a selective reagent seems timely.…”
Section: Discussionmentioning
confidence: 99%
“…This progress contains amplified T cell migrating into allergic lung and memory T cells back to lymph nodes (LN). After exposure to allergen, the number of T cells in the airways increases dramatically, amplifying allergic inflammation (Lommatzsch et al, 2006;Thomas et al, 2007). Experiments in animal models have demonstrated that, following allergen challenge, antigen specific T cells in the airways do not proliferate but are recruited into the lung from regional lymph nodes, leading to the increase in T cells in the airways (Harris et al, 2002).…”
Section: Th2 Cell and Allergy Asthmamentioning
confidence: 99%